2000
DOI: 10.1002/1096-9861(20001030)426:4<632::aid-cne10>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Do subplate neurons comprise a transient population of cells in developing neocortex of rats?

Abstract: Studies were undertaken to determine whether neurons of the subplate layer represent a transient or stable population of cells in developing neocortex of rat. The first set of studies sought to determine the fraction of subplate neurons that is lost during early postnatal development. The optical dissector method was used to analyze fluorescently stained material in animals the age of postnatal day 0 (P0) to P40. These results demonstrate a reduction of slightly less than half of the total number of subplate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 73 publications
3
43
0
Order By: Relevance
“…In rats, however, a considerable fraction of subplate neurons seem to survive like other cortical plate cells (Robertson et al, 2000). These anatomical results are consistent with BrdU labeling, suggesting the survival of subplate and superplate neurons at P10.…”
Section: Roles Of Early Generated Transient Synapses For Development supporting
confidence: 80%
“…In rats, however, a considerable fraction of subplate neurons seem to survive like other cortical plate cells (Robertson et al, 2000). These anatomical results are consistent with BrdU labeling, suggesting the survival of subplate and superplate neurons at P10.…”
Section: Roles Of Early Generated Transient Synapses For Development supporting
confidence: 80%
“…Initial studies (Sugita, 1917) had already demonstrated that the rodent subplate is not really a transient structure, but a well defined layer (VIb or VII) which persists as a part of the 'traditional' cortex throughout the rodent lifespan. In recent years, the rodent subplate ⁄ layer VII has been increasingly recognized as a 'special case' probably characteristic for this specific group of mammals and with significantly different developmental history and postnatal roles in comparison with primates and humans (Reep & Goodwin, 1988;Reep, 2000;Valverde et al 1989Valverde et al , 1995Robertson et al 2000;Clancy & Cauller, 1999;Clancy et al 2001Clancy et al , 2009Arias et al 2002;Tomioka et al 2005).…”
Section: Lessons From History -New Trends In Subplate Researchmentioning
confidence: 99%
“…A period of programmed cell death in embryonic SP neurons has been demonstrated (Allendoerfer and Shatz, 1994;Robertson et al, 2000). To determine whether similar changes occur in the SP and WM regions, cells were immunolabeled using MAP-2 and NeuN between P2 and P30.…”
Section: Changes In Neuronal Density In Sp and Wmmentioning
confidence: 99%
“…Alternatively, because some SP neurons (ϳ20%) survive, they may perform other functions in the postnatal neocortex, becoming integrated into the microcircuitry of the six major cortical laminase. Data in support of this alternative include the following: fluorescent tracers applied to layer I in juvenile and adult rats retrogradely label somata of SP and WM cells (Clancy and Cauller, 1999); SP neurons that survive programmed cell death do not show evidence of atrophy of their dendritic trees or nuclear shrinkage (Robertson et al, 2000); and SP cells receive functional synaptic input during the first days [postnatal day 0 (P0) to P3] of postnatal life in the rat (Hanganu et al, 2001(Hanganu et al, , 2002. However, the fate and functional properties of these cells beyond the immediate perinatal period are unknown.…”
Section: Introductionmentioning
confidence: 99%